2017
DOI: 10.1176/appi.ps.201600134
|View full text |Cite
|
Sign up to set email alerts
|

Using Peer Navigators to Address the Integrated Health Care Needs of Homeless African Americans With Serious Mental Illness

Abstract: Objective Impact of a peer navigator program (PNP) develop by a community based participatory research team was examined on African Americans with serious mental illness who were homeless. Methods Research participants were randomized to PNP or a treatment-as-usual control group for one year. Data on physical and mental health, recovery, and quality of life were collected at baseline, 4, 8 and 12 months. Results Findings from group by trial ANOVAs of omnibus measures of the four constructs showed significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(127 citation statements)
references
References 40 publications
2
79
0
Order By: Relevance
“…Interaction effects (a nonsignificant trend for scheduled appointments and a significant change for achieved appointments) suggested that there was a steady increase in appointments for the PNP group compared with the control group. This change was similar to the findings of previous research on a PNP for African Americans with serious mental illness (15). Peer navigators seem to help people with serious mental illness better engage with varied health services.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Interaction effects (a nonsignificant trend for scheduled appointments and a significant change for achieved appointments) suggested that there was a steady increase in appointments for the PNP group compared with the control group. This change was similar to the findings of previous research on a PNP for African Americans with serious mental illness (15). Peer navigators seem to help people with serious mental illness better engage with varied health services.…”
Section: Discussionsupporting
confidence: 85%
“…This may have occurred because a similar increase in service engagement (scheduled and achieve appointments) was noticed at that time. This finding echoes the positive results of the earlier PNP study on African Americans with serious mental illness (15). Engaging Latinos with serious mental illness in existing health care services through peer navigators is an important aid in addressing health and recovery needs.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Strategies for recruitment and group assignment, as well as specification of the PNP, were described elsewhere (Corrigan et al, 2016). Research participants were 39% female ( N =26) and 52.9 ± 8.0 years old on average.…”
Section: Methodsmentioning
confidence: 99%
“…72,86 In an RCT of African Americans with severe mental illness who were experiencing homelessness, participants receiving peer navigation demonstrated improvements in selfreported physical and mental health status and quality of life compared with participants receiving treatment as usual. 87 Additionally, a study in an adult mental health inpatient setting found that patients working with professional navigators showed significantly better clinical outcomes than those receiving treatment as usual, including greater improvement on measures of psychopathology and distress, less time spent in the ICU, and lower rates of readmission in the month after discharge. 88 In the study referenced above of children with emotional disturbances receiving special education services, children in families receiving peer navigation received fewer suspensions.…”
Section: Navigation Outcomes Researchmentioning
confidence: 99%